3 - Cows, Cash and Terror: How Cattle Rustling Proceeds Fuel Boko Haram Insurgency in Nigeria - Okoli, Al Chukwuma (Africa Development, 2019)
This study explores the nexus between cattle rustling and the Boko Haram insurgency by way of ascertaining how proceeds from the former is used to fund the latter. By means of secondary research, predicated on the theory of terrorism financing the article argues that material and financial proceeds from cattle rustling have been deployed to fund and sustain Boko Haram operations. The study underscores the strategic implications of cattle rustling as a veritable source of terrorism financing, and contends that dismantling cattle rustling infrastructure (the sources, syndicates, networks, markets, routes, transits, etc.) is key to counter-insurgency efforts in Nigeria.